Visual Review of Periodic Print Media Advertising in Bandung, West Java 1970 Decade - Heryadi, Heddy (VCD: Journal of Visual Communication Design, 2017)
Since Dutch plantation owners in West Java established and developed the city of Bandung, they settled in the area of the city and also making periodical print media for socialization and communication among them. In the past 1930 decade the Dutch colonial start to create and form the printed media and publications in a steady and continuous way in West Java. After the independence declaration of Indonesia State in 1945, the print media and periodical publications continued and remade by the Chinese and indigenous communities. The area of Bandung became more advanced into a business city after World War II, in which formed commercial enterprises and other social activities. During the period of Indonesia government shifting from “orde Lama” to “orde baru” the activities of printing and publishing as a network of communication media increasingly established and widely established. In West Java, newspapers and magazines such as; "Pikiran Rakyat" and "Mangle" has been read and watched by many societies in Bandung city, even nationally used as a means of advertising for readers. "Pikiran Rakyat" and "Mangle" are created and developed by publishers who have Sundanese / Sundanese influence. As is known Sundanese race / tribe is the second largest number of tribes in the Indonesia region. The research methodology was conducted with a qualitative descriptive approach and discusses the visual documentation data from the periodical publishing archive of the 1970s decade. In this concern, the author is interested to review the periodical print media in terms of visual display advertising of 1970 decade. Besides to review visual graphic design the other purposes are in an effort to document the visual data, for information for the next Indonesia generation.